2010
DOI: 10.1002/etc.402
|View full text |Cite
|
Sign up to set email alerts
|

Review of recent proteomic applications in aquatic toxicology

Abstract: Abstract-Over the last decade, the environmental sciences have witnessed an incredible movement towards the utilization of highthroughput molecular tools that are capable of detecting simultaneous changes of hundreds, and even thousands, of molecules and molecular components after exposure of organisms to different environmental stressors. These techniques have received a great deal of attention because they not only offer the potential to unravel novel mechanisms of physiological and toxic action but are also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 80 publications
0
55
0
Order By: Relevance
“…This is followed by mass spectrometry (MS) analyses to identify specific proteins (Zhang et al, 2013). After the first application in aquatic toxicology by and who analyzed the proteomic response of mussels (Mytilus edulis) exposed to polychlorinated biphenyls, copper, and salinity stress, proteomic techniques have been widely applied to fishes as well as other aquatic invertebrates (Sanchez et al, 2011).…”
Section: Toxicogenomics In Aquatic Toxicology Studiesmentioning
confidence: 99%
“…This is followed by mass spectrometry (MS) analyses to identify specific proteins (Zhang et al, 2013). After the first application in aquatic toxicology by and who analyzed the proteomic response of mussels (Mytilus edulis) exposed to polychlorinated biphenyls, copper, and salinity stress, proteomic techniques have been widely applied to fishes as well as other aquatic invertebrates (Sanchez et al, 2011).…”
Section: Toxicogenomics In Aquatic Toxicology Studiesmentioning
confidence: 99%
“…The use of proteomics to detect the effects of contaminants on physiological mechanisms is a relatively new and sensitive approach that can assist in understanding the impacts of xenobiotics on aquatic organisms [132][133][134]. Proteomics has much to offer even in species used in ecotoxicological studies that are poorly represented in sequence databases.…”
Section: Biomarkers For Reproductive Toxicity From Contaminant Exposurementioning
confidence: 99%
“…Protein spots can be matched by searching sequence databases for similar but not necessarily identical proteins. To date, the proteomic studies with aquatic invertebrates that have not been sequenced have identified on average only 15 proteins, highlighting the problem with matching amino acid sequences across species [134]. Recently, a few studies have appeared using proteomics in ecotoxicological research on crustacean species with nonsequenced genomes, including three amphipod species [135][136][137].…”
Section: Biomarkers For Reproductive Toxicity From Contaminant Exposurementioning
confidence: 99%
“…Proteomic analysis, a powerful tool for global evaluation of protein expression, has been widely used in aquatic toxicology. Several previous studies have focused on the application of quantitative proteomics for identifying and quantifying differentially expressed proteins in response to EDCs (Biales et al, 2011;De Wit et al, 2010;Fang et al, 2010;Martyniuk et al, 2009Martyniuk et al, , 2010Martyniuk et al, , 2012bRalston-Hooper et al, 2012;Sanchez et al, 2011). Hundreds of proteins were identified in these studies; however few of them have been systematically analyzed for their correlation with endocrine disruption.…”
Section: Introductionmentioning
confidence: 99%